The Ohio frontier : crucible of the Old Northwest, 1720-1830 - Hurt, R. Douglas (History of the trans-Appalachian frontier., 1998)
The Ohio Frontier Crucible of the Old Northwest, 1720'1830 R. Douglas Hurt "This exhaustively researched and well-written book provides a comprehensive history of Ohio from 1720 to 1830." 'Journal of the Early Republic Nowhere on the American frontier was the clash of cultures more violent than in the Ohio country. There, Shawnees, Wyandots, Delawares, and other native peoples fought to preserve their land claims against an army that was incompetent at the beginning but highly trained and disciplined in the end. Sales territory is worldwide A History of the Trans-Appalachian Frontier 1996; 440 pages, 23 b & w photos, 7 maps, bibl. essay, index, 6 x 9 cloth 0-253-33210-9 $39.95 L / 28.50 paper 0-253-21212-X $19.95 t / 14.50